Assessment of the Economic Contributions of the NCE Students’ Farm Practical Training Programme to Agricultural Production in Ilorin, Kwara State, Nigeria - Ogundele, Oyekanmi Olugbenga; Ojo, Adesanmi (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
One essential skill-building programme for agricultural science students is farm practical training, which is meant to help them become knowledgeable and independent. This study, therefore, aims to assess the economic impact of students' farm practical training programmes on agricultural production in Kwara State, Nigeria. Employing an Expo Facto design, the research takes a comprehensive approach by examining both the direct and indirect contributions of these programmes to the local economy. A random sample comprising 80 NCE students was drawn from the population of students at Kwara State College of Education, Ilorin, Kwara State, Nigeria. Data were subsequently gathered using a questionnaire titled "Economic Contribution of NCE Students Farm Practical Training Programme to Agricultural Production, (ECSFPTPAP) and subjected to descriptive statistics of mean rating. The study showed a high level of farm practical training among NCE students in the Kwara State College of Education, Ilorin. Furthermore, this study established a significant economic contribution of NCE students' farm practical training programs to agricultural production. These results indicate a positive impact of integrating farm practical training into the NCE curriculum on agricultural output within Kwara State. Based on these findings, it is recommended that Kwara State College of Education, Ilorin, prioritise the provision of adequate facilities to enable students to translate theoretical knowledge into practical farming skills. Creating a supportive environment for agricultural practice would, in turn, further enhance the economic benefits derived from farm practical training, contributing to increased agricultural production in Kwara State, Nigeria.